Organic pest management of hill crops through locally available plant extracts in the mid‐Himalayas. (27th June 2022) - Stanley, Johnson; Subbanna, ARNS; Mahanta, Dibakar; Paschapur, Amit Umesh; Mishra, Krishna Kant; Varghese, Eldho
Abstract: The present investigation was aimed to assess the best organic pest management practices in soybean and Indian rape cultivation systems in the mid‐Himalayas. Based on the preliminary laboratory assays, promising treatments were selected for field assays for 3 years. It was observed that Parthenium leaf extract 5% provided significantly higher pest reduction in field condition with 76.8% at 7 DAT (days after treatment) against sucking bug, Chauliops choprai infesting soybean. In case of mustard aphids ( Lipaphis erysimi ) infesting Indian rape, Nimbicidine 5 ml L −1 was found superior with 61.5% pest reduction, followed by 5% seed extract of Melia azedarach at 7 DAT in field condition. Contrary to pest reduction, the pooled yield data analysis showed that among organic treatments, spraying of Nimbicidine @ 5 ml L −1 recorded significantly superior yield over control with yield advantage of 29%, followed by M. azedarach seed extract 5% and 10%, both recording 21% yield advantage in case of soybean. Nimbicidine was also superior for Indian rape crop with yield advantage of 51%, followed by Beauveria bassiana @ 3 g L −1 with 44% and 5% seed extract of M. azedarach with 33% yield advantage compared to control. Hence, Parthenium leaf extract 5% and Nimbicidine are recommended for effective control of C. choprai and L . erysimi infesting soybean and Indian rape, respectively. But to achieve higher yield, Nimbicidine is the best among organic management of those pests for both crops. These results suggest good organic pest management options in organic farming system. Abstract : Parthenium leaf extract 5% yielded higher pest reduction against soybean sucking bug. Nimbicidine 0.03% was the superior treatment against toria aphid, Lipaphis erysimi . Nimbicidine 0.03% recorded higher yield advantage over control in soybean and toria. Melia azedarach 5% was the next superior organic treatment after Nimbicidine 0.03%. Plant extracts are suitable organic treatments in organic soybean and toria system.